2010
DOI: 10.1128/jvi.01350-09
|View full text |Cite
|
Sign up to set email alerts
|

Inability of Plasmacytoid Dendritic Cells To Directly Lyse HIV-Infected Autologous CD4 + T Cells despite Induction of Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand

Abstract: The function of plasmacytoid dendritic cells (PDC) in chronic human immunodeficiency virus type 1 (HIV-1) infection remains controversial with regard to its potential for sustained alpha interferon (IFN-␣) production and induction of PDC-dependent tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL)-mediated cytotoxicity of HIV-infected cells. We address these areas by a study of chronically HIV-1-infected subjects followed through antiretroviral therapy (ART) interruption and by testing PDC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…A previous report demonstrated that the HIV stimulation of pDCs induces a high level of production of IFN-␣ and a rapid expression of TRAIL, transforming them into IFN-producing killer pDCs (iKpDCs) (5). It was also shown previously that despite TRAIL expression, pDCs could not induce the lysis of autologous CD4 ϩ T cells (1). However, in the present work, when primary HIV-infected autologous CD4 ϩ T cells were used as target cells, we also observed apoptosis induced by both unstimulated and TLR-9-stimulated pDCs.…”
Section: Fig 4 Pdc-mediated Hiv-infected Primary Autologous Cd4mentioning
confidence: 99%
“…A previous report demonstrated that the HIV stimulation of pDCs induces a high level of production of IFN-␣ and a rapid expression of TRAIL, transforming them into IFN-producing killer pDCs (iKpDCs) (5). It was also shown previously that despite TRAIL expression, pDCs could not induce the lysis of autologous CD4 ϩ T cells (1). However, in the present work, when primary HIV-infected autologous CD4 ϩ T cells were used as target cells, we also observed apoptosis induced by both unstimulated and TLR-9-stimulated pDCs.…”
Section: Fig 4 Pdc-mediated Hiv-infected Primary Autologous Cd4mentioning
confidence: 99%
“…HIV, human T cell leukemia virus-1, and influenza virus, all natural ligands of TLR7, trigger a pDC innate immune response that not only involves the massive production of IFN-a, but also the upregulation of functionally active TRAIL (TRAIL/ Apo-2L/TNFSF10) (8)(9)(10). TRAIL is also expressed by HIVinfected pDCs (8,11,12), and, notably, TRAIL + pDCs may kill CD4 + T cells isolated from HIV-infected patients (12) and thus perhaps contribute to T cell depletion during HIV viremia. In addition to their role in viral immunity, several studies propose a direct role for cytotoxic pDCs in antitumor immunity.…”
Section: Hla-drmentioning
confidence: 99%
“…15,[20][21][22] Induction of IFN-a by PDCs by various stimuli is directly related to the extent of down-regulation of the C-type lectin surface receptor BDCA-2 expressed on PDCs. 23 Thus, crosslinking or ligation of BDCA-2 with anti-BDCA-2 monoclonal antibodies (mAbs) has been reported to suppress IFN-a production by PDCs via TLR9 ligands such as HSV and CpGODNs [23][24][25][26] and to a much lesser extent via a TLR7 ligand such as influenza virus.…”
Section: Introductionmentioning
confidence: 99%